Comparative view for the impact of five eco factors on species distribution and weed community structure in Isthmus of Suez and adjoining farmland east Nile delta, Egypt - Alaa M.M.A. Mahgoub (Heliyon, 2019)
The study of the extent of variability and the order of importance for the impact of environmental factors on species distribution and weed community structure from one region to the other is an interesting research subject. The present study aimed to discuss the issue to give a comparative view with the author's findings about the impact of the prevailing climate, soil type, crop type, crop sustainability and urbanization on species distribution and weed community structure in the coastal farmland and adjacent territories in northwest delta region (Mahgoub, 2019). A new sample area selected and comprised the reclaimed land of El Ballah region in Isthmus of Suez and adjoining farmland east Nile delta. A total of 245 species were recorded. Agglomerative Hierarchical Clustering (AHC) identified four vegetative sociation groups (VSG). The diversity of the four identified VSG or weed communities was evaluated at different levels. Parincipal Component Analysis (PCA) indicated the influence of the five eco factors on species distribution and variability of weed community structure, summarized the relationships among variables and investigated the proximity among samples and how they related to variables. ANOVA followed by Tukey's test were applied twice for the resulted VSG, one depending on soil variables as explanatory variables and the other on sampling site's indicative scores for the five eco factors. The results of ANOVA (R2, F, P), sample variance (S2) and other multivariate analyses indicated a different order of importance for the impact of the five eco factors in comparable to the former study denoted above. The soil type was the most impacting factor on species distribution and weed community structure, followed by crop type, crop sustainability, prevailing climate and urbanization, respectively.